2022
DOI: 10.1101/2022.01.24.477584
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Does the impact of cultivar mixtures on virulence dynamics in Zymoseptoria tritici populations persist after interseason sexual reproduction?

Abstract: This study follows on from a previous study showing that binary mixtures of wheat cultivars affect the evolution of Zymoseptoria tritici populations within a field epidemic from the beginning (t1) to the end (t2) of a growing season. Here, we focused on the impact of interseason sexual reproduction on this evolution. We studied mixtures of susceptible and resistant cultivars (carrying Stb16q, a recently broken-down resistance gene) in proportions of 0.25, 0.5 and 0.75, and their pure stands. We determined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…A recent field experiment suggested that a mixture can maintain the efficacy of the resistance encoded by Stb16q through a decrease in the frequency of virulent strains infecting the susceptible cultivar and an increase in the frequency of avirulent strains occurring on the cultivar carrying Stb16q in the mixtures compared to pure stands. The observed changes resulted (i) on the one hand from virulence selection/counter‐selection driven by exchanges of splash‐dispersed asexual spores between cultivars depending on their respective proportions in the mixture (Orellana‐Torrejon, Vidal, Boixel, et al, 2022), and (ii) on the other hand from sexual reproduction between virulent strains and avirulent strains that land on the cultivar carrying Stb16q and then recombine with virulent strains without the need to infect host tissues (Orellana‐Torrejon, Vidal, Saint‐Jean, & Suffert, 2022). This mechanism that explains the persistence (or even a slight increase) of avirulent strains in mixtures was experimentally established by Orellana‐Torrejon, Vidal, Gazeau, et al (2022), who showed that symptomatic asexual infection is not required for a strain to engage in sexual reproduction [a similar finding was also reported for the Stb6‐AvrStb6 interaction (Kema et al, 2018)].…”
Section: Discussionmentioning
confidence: 99%
“…A recent field experiment suggested that a mixture can maintain the efficacy of the resistance encoded by Stb16q through a decrease in the frequency of virulent strains infecting the susceptible cultivar and an increase in the frequency of avirulent strains occurring on the cultivar carrying Stb16q in the mixtures compared to pure stands. The observed changes resulted (i) on the one hand from virulence selection/counter‐selection driven by exchanges of splash‐dispersed asexual spores between cultivars depending on their respective proportions in the mixture (Orellana‐Torrejon, Vidal, Boixel, et al, 2022), and (ii) on the other hand from sexual reproduction between virulent strains and avirulent strains that land on the cultivar carrying Stb16q and then recombine with virulent strains without the need to infect host tissues (Orellana‐Torrejon, Vidal, Saint‐Jean, & Suffert, 2022). This mechanism that explains the persistence (or even a slight increase) of avirulent strains in mixtures was experimentally established by Orellana‐Torrejon, Vidal, Gazeau, et al (2022), who showed that symptomatic asexual infection is not required for a strain to engage in sexual reproduction [a similar finding was also reported for the Stb6‐AvrStb6 interaction (Kema et al, 2018)].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the use of cultivar mixtures would increase the exposure of plants carrying a resistance gene to the corresponding avirulent strains, due to the presence of neighbouring susceptible plants on which these strains would be then able to multiply asexually. Orellana-Torrejon et al (2022a, 2022b highlighted a consequence of this phenomenon in the field: the frequency of avirulent Z. tritici strains was higher after sexual reproduction on the residues of a resistant wheat cultivar grown in a mixture than after sexual reproduction on the residues of a pure stand, providing experimental evidence of an "overtransmission" of avirulence to the next epidemic season. Cultivar mixtures, therefore, appear to be a promising way to exploit the epidemiological consequences of avirulent strains crossing on resistant cultivars for limiting the breakdown of resistance genes.…”
Section: Epidemiological Consequences For Avirulent Strains Reproduci...mentioning
confidence: 99%
“…However, cultivar mixtures can still effectively control STB and limit the loss in effective- Torrejon et al, 2022b). This mechanism that explains the persistence (or even a slight increase) of avirulent strains in mixtures was experimentally established by Orellana-Torrejon et al (2022c), who showed that symptomatic asexual infection is not required for a strain to engage in sexual reproduction [a similar finding was also reported for the Stb6-AvrStb6 interaction (Kema et al, 2018)].…”
Section: Implications For Field-scale Strategies Of Disease Managementmentioning
confidence: 76%
“…A recent field experiment suggested that a mixture can maintain the efficacy of the resistance encoded by Stb16q through a decrease in the frequency of virulent strains infecting the susceptible cultivar and an increase in the frequency of avirulent strains occurring on the cultivar carrying Stb16q in the mixtures compared to pure stands. The observed changes resulted (i) on the one hand from virulence selection/counter-selection driven by exchanges of splash-dispersed asexual spores between cultivars depending on their respective proportions in the mixture (Orellana-Torrejon et al, 2022a), and (ii) on the other hand from sexual reproduction between virulent strains and avirulent strains that land on the cultivar carrying Stb16q and then recombine with virulent strains without the need to infect host tissues (Orellana-Torrejon et al, 2022b). This mechanism that explains the persistence (or even a slight increase) of avirulent strains in mixtures was experimentally established by Orellana-Torrejon et al (2022c), who showed that symptomatic asexual infection is not required for a strain to engage in sexual reproduction [a similar finding was also reported for the Stb6-AvrStb6 interaction (Kema et al, 2018)].…”
Section: Discussionmentioning
confidence: 99%